2021
DOI: 10.1093/hmg/ddab125
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomics analysis reveals a 21q22.11 locus contributing risk to COVID-19

Abstract: The systematic identification of host genetic risk factors is essential for the understanding and treatment of coronavirus disease 2019 (COVID-19). By performing a meta-analysis of two independent genome-wide association summary datasets (N = 680 128), a novel locus at 21q22.11 was identified to be associated with COVID-19 infection (rs9976829 in IFNAR2-IL10RB, odds ratio = 1.16, 95% confidence interval = 1.09–1.23, P = 2.57 × 10−6). The rs9976829 represents a strong splicing quantitative trait locus for both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 64 publications
2
62
0
Order By: Relevance
“…Furthermore, the index SNP of rs505922 (P = 2.24×10 −9 ) in the 9q34.2 locus is highly LD with the reported SNP of rs657152 (R 2 = 0.874) [27] and rs8176719 (R 2 = 0.876) [25]. Based on the top-ranked V2G score for rs505922, we prioritized ABO as a potential causal gene contributing susceptibility to severe COVID-19.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the index SNP of rs505922 (P = 2.24×10 −9 ) in the 9q34.2 locus is highly LD with the reported SNP of rs657152 (R 2 = 0.874) [27] and rs8176719 (R 2 = 0.876) [25]. Based on the top-ranked V2G score for rs505922, we prioritized ABO as a potential causal gene contributing susceptibility to severe COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…The result of a network-based enrichment analysis suggested that 22 of 34 risk genes were significantly enriched in a PPI subnetwork (P = 2.85×10 −13 , Figure 2D), which is consistent with the consensus that disease-related genes are more densely connected [50, 51]. To functionally characterize the drug targets of these genes, we conducted a drug-gene interaction analysis and identified 11 genes including CCR1, IFNAR2, IL10RB , and OAS1 were targeted by at least one known drug (Figure 2D and Supplemental Figure S14), of which some genes including CCR1, IFNAR2 , and IL10RB have been reported to be drug targets for treating severe COVID-19 patients [25, 26]. Furthermore, these 34 genes were significantly enriched in a functional module consisting of 10 biological pathways (Figure 2E, Supplemental Table S8 and Figure S13), among which two top-ranked ones being cytokine-cytokine receptor interaction and chemokine signaling pathway (FDR < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods provide an interface between genetic epidemiological data and molecular phenotypes, such as cell-specific gene expression, active chromatin markers, DNA methylation and chromosome interactions, and allow one to assess the enrichment of genetic associations with various functional ontologies. These methods can be used to demonstrate enrichment of specific gene ontologies, like neurogenesis and locomotor behaviour in restless legs syndrome [2], cytokine signalling pathways for COVID-19 [138], cell growth and synapse organisation for volume of lateral nuclei [139] and cell adhesion and transsynaptic signalling for Tourette syndrome [140]. Hormozdiari et al, applied S-LDSC on sets of functional SNPs (eQTLs, etc.,) and found that they are indeed enriched for heritability in an expected, cell type-specific manner [141].…”
Section: Interpretabilitymentioning
confidence: 99%